Zingiber officinale rhizome extracts mediated ni nanoparticles and its promising biomedical and environmental applications - Abdullah; Tahir Hussain; Shah Faisal; Muhammad Rizwan; Mervt M. Almostafa; Nancy S. Younis; Galal Yahya (BMC, 2023)
Abstract Background Zingiber officinale, generally known as ginger, contains bioactive phytochemicals, including gingerols and shogaols, that may function as reducing agents and stabilizers for the formation of nickel nanoparticles (Ni-NPs). Ginger extract-mediated nickel nanoparticles were synthesized using an eco-friendly method, and their antibacterial, antioxidant, antiparasitic, antidiabetic, anticancer, dye degrading, and biocompatibility properties were investigated. Methods UV-visible spectroscopy, fourier transform infrared spectroscopy, X-ray powder diffraction, energy-dispersive X-ray spectroscopy, and scanning electron microscopy were used to validate and characterize the synthesis of Ni-NPs. Agar well diffusion assay, alpha-amylase and glucosidase inhibitory assay, free radical scavenging assay, biocompatibility assay, and MTT assay were used to analyse the biomedical importance of Ni-NPs. Results SEM micrograph examinations revealed almost aggregates of Ni-NPs; certain particles were monodispersed and spherical, with an average grain size of 74.85 ± 2.5 nm. Ni-NPs have successfully inhibited the growth of Pseudomonas aeruginosa, Escherichia coli, and Proteus vulgaris by inducing membrane damage, as shown by the absorbance at 260 nm (A260). DPPH (2,2-diphenyl-1-picrylhydrazyl) free radicals were successfully scavenged by Ni-NPs at an inhibition rate of 69.35 ± 0.81% at 800 µg/mL. A dose-dependent cytotoxicity of Ni-NPs was observed against amastigote and promastigote forms of Leishmania tropica, with significant mortality rates of 94.23 ± 1.10 and 92.27 ± 1.20% at 1.0 mg/mL, respectively. Biocompatibility studies revealed the biosafe nature of Ni-NPs by showing RBC hemolysis up to 1.53 ± 0.81% at 400 µg/mL, which is considered safe according to the American Society for Materials and Testing (ASTM). Furthermore, Ni-NPs showed antidiabetic activity by inhibiting α-amylase and α-glucosidase enzymes at an inhibition rate of 22.70 ± 0.16% and 31.23 ± 0.64% at 200 µg/mL, respectively. Ni-NPs have shown significant cytotoxic activity by inhibiting MCF-7 cancerous cells up to 68.82 ± 1.82% at a concentration of 400 µg/mL. The IC50 for Ni-NPs was almost 190 µg/mL. Ni-NPs also degraded crystal violet dye up to 86.1% at 2 h of exposure. Conclusions In conclusion, Zingiber officinale extract was found successful in producing stable nanoparticles. Ni-NPs have shown substantial biomedical activities, and as a result, we believe these nanoparticles have potential as a powerful therapeutic agent for use in nanomedicine.